(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Sustainable agricultural development has become a key priority for the Republic of Uzbekistan in the context of increasing environmental challenges, economic transformation, and global food security concerns. As a country with limited water resources and a predominantly arid climate, Uzbekistan faces significant constraints in maintaining agricultural productivity while ensuring environmental sustainability. At the same time, ongoing reforms aimed at liberalizing the agricultural sector and promoting market-oriented mechanisms create new opportunities for growth and modernization.